2014
DOI: 10.1159/000360869
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Xylitol in a School-Based Cluster-Randomized Clinical Trial

Abstract: Objective: The purpose of this double-blind, cluster-randomized clinical trial was to examine the effects of xylitol gummy bear snacks on dental caries progression in primary and permanent teeth of inner-city school children. Methods: A total of 562 children aged 5-6 years were recruited from five elementary schools in East Cleveland, Ohio. Children were randomized by classroom to receive xylitol (7.8 g/day) or placebo (inulin fiber 20 g/day) gummy bears. Gummy bears were given three times per day for the 9-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 27 publications
1
43
0
2
Order By: Relevance
“…Todos os dentifrícios apresentaram efeito antimicrobiano contra S. mutans(p < 0,001). Existiu diferença significante entre os dentifrícios fluoretados, de modo que o dentifrício Aquafresh apresentou a maior atividade antimicrobiana (22,48±1,59), seguido do dentifrício Tandy (20 …”
Section: Resultsunclassified
See 1 more Smart Citation
“…Todos os dentifrícios apresentaram efeito antimicrobiano contra S. mutans(p < 0,001). Existiu diferença significante entre os dentifrícios fluoretados, de modo que o dentifrício Aquafresh apresentou a maior atividade antimicrobiana (22,48±1,59), seguido do dentifrício Tandy (20 …”
Section: Resultsunclassified
“…Da mesma forma, Mickenautsch, Yengopal 9 realizaram uma revisão sistemática e sugeriram que a utilização de xilitol associado com fluoreto pode ser benéfica na prevenção da cárie dentária. Por sua vez, Lee et al 20 demonstraram em um ensaio clínico randomizado que a utilização de gomas de mascar contendo xilitol não apresentou benefício adicional a outras medidas preventivas, como por exemplo o uso de fluoretos, em comparação ao placebo. Estudos demonstrando o efeito de dentifrícios contendo xilitol associado ao flúor em comparação a dentifrícios que contém apenas o flúor, ainda são considerados com baixa evidência científica, o que justifica o desenvolvimento de estudos clínicos randomizados com maior qualidade 21,22 .…”
Section: Discussionunclassified
“…Alternatively, xylitol can be introduced into the oral environment of kindergarten and school children in the form of a gummy-bear snack [28][29][30]. Ly et al [29] evaluated the efficiency of the administration 3 times a day of such snacks containing doses of xylitol, in total reaching up to 15.9 g and 11.7 g, and 44.7 g maltitol, on the levels of S. mutans, S. sobrinus and Lactobacilli spp.…”
Section: Prevention Of Caries Development In Permanent Teeth In Childrenmentioning
confidence: 99%
“…bacteria. Instead, Lee et al [30], administering xylitol (7.8 g/day) to 5-6-year-old children 3 times a day within 9 months, or alternatively a placebo (inulin, 20 g/day) in the form of gummy bears, found a lower caries incidence in children that were receiving xylitol.…”
Section: Prevention Of Caries Development In Permanent Teeth In Childrenmentioning
confidence: 99%
“…A systematic review assessing the caries-preventive effect of consuming xylitol-based candies and lozenges concluded that a reduction in caries increment could be observed in 2 out of 3 intervention groups [Gonçalves Antonio et al, 2011]. However, some recent intervention trials did not confirm a significant effect on caries development associated with xylitol lozenge/candy consumption in children [Lenkkeri et al, 2012;Lee et al, 2015] or adults [Fontana and Gonzalez-Cabezas, 2013]. In recent years, erythritol, a polyol of the tetritol type, has been shown to have a similar effect on caries risk factors as previously reported for xylitol [Kawanabe et al, 1992;Mäkinen et al, 2005].…”
mentioning
confidence: 99%